Synthesis and characterization of mesoporous microspherical particles for drug delivery applications. (2020) - Aggarwal, Anoop; Jolly, Sukhwinder Singh; Singh, Ravinder Pal
Abstract: Hierarchically assembled Hydroxyapatite (HAP) mesoporous particles were synthesized using a facile hydrothermal method. Products were comprehensively characterized using XRD, FTIR, FESEM and BET techniques. XRD confirmed the monolithic apatitic composition of particles. FTIR corroborated the XRD phase analysis and confirmed the carbonates structure of synthesized particles. FESEM suggested the 3D nanostructured microspherical shaped particles. The nitrogen isotherms also confirmed the formation of elongated particles with inherent mesoporous structure. The synthesized particles can be effectively employed in various multifunctional applications including drug delivery and tissue regeneration applications.